Pengaruh Penguasaan Kosakata terhadap Kemampuan Membaca Teks Persuasif Bahasa Inggris Siswa Kelas X SMK Negeri 2 Depok - Prima Pantau Putri Santosa (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
The goal of this research is to analyse and prove the effect of vocabulary mastery on students’English persuasive text reading competency at the 10th grade of SMK Negeri 2 Depok. Research data was collected by giving multiple cohoice tests of vocabulary mastery and persuasive text reading competency. Furthermore, the data was analyzed quantitatively in order to know correlation coefficient, determination coefficient and signifinancy coefficient as part of hypothesis test. Data analysis was conducted with ? = 0,05. Based on the result of hypothesis test, the researcher has found the significant effect of vocabulary mastery on students’ English persuasive text reading competency.